2009
DOI: 10.1086/593940
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Psychological and School Organizational and Leadership Factors on Teachers' Professional Learning in Dutch Schools

Abstract: The effect of teacher psychological, school organizational and leadership factors on teachers' professional learning in Dutch schools Geijsel, F.P.; Sleegers, P.J.C.; Stoel, R.D.; Kruger, M.L. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
428
7
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(521 citation statements)
references
References 52 publications
32
428
7
24
Order By: Relevance
“…Teachers' perceptions of workplace conditions Studies on school organizational conditions have already shown that psychological factors mediate the impact of these conditions on teachers' engagement in professional learning; for example, through teachers' commitment and self-efficacy (Kwakman 2003, Geijsel et al 2009, Thoonen et al 2011. Similarly, the objective workplace conditions alone do not influence teachers' learning; it is how teachers make sense of their workplace as a learning environment, and as a consequence use the learning opportunities afforded by this environment (Coburn 2001, Hoekstra et al 2009, Tynjälä 2012.…”
Section: Workplace Conditions Of Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' perceptions of workplace conditions Studies on school organizational conditions have already shown that psychological factors mediate the impact of these conditions on teachers' engagement in professional learning; for example, through teachers' commitment and self-efficacy (Kwakman 2003, Geijsel et al 2009, Thoonen et al 2011. Similarly, the objective workplace conditions alone do not influence teachers' learning; it is how teachers make sense of their workplace as a learning environment, and as a consequence use the learning opportunities afforded by this environment (Coburn 2001, Hoekstra et al 2009, Tynjälä 2012.…”
Section: Workplace Conditions Of Schoolsmentioning
confidence: 99%
“…Furthermore, in recent studies it is argued that it is not so much the objective conditions which support or impede employees' professional learning, but the way they interpret those organizational conditions in relation to their work and learning (Nishii and Wright 2007, Hoekstra et al 2009, Tynjälä 2012, Imants et al 2013). Previously, a few studies have demonstrated how mediating psychological factors on the part of the individual might impact the relation between structural and cultural dimensions of the school organization and teachers' professional learning (Kwakman 2003, Geijsel et al 2009, Thoonen et al 2011. Thus, it is of interest how teachers' perceptions of the workplace environment can be understood as affecting professional learning.…”
Section: Introductionmentioning
confidence: 99%
“…Third, most studies of PLCs acknowledge the importance of stimulating and participative leadership as a key dimension that is part of the organizational capacity that fosters PLCs. This dimension refers to the degree to which school and departmental leaders support and stimulate teacher learning, delegate responsibilities, and share leadership functions (Geijsel, Sleegers, Stoel, & Krüger, 2009;Geijsel, Sleegers, Van den Berg, & Kelchtermans, 2001;Mitchell & Sackney, 2000;Moolenaar, Daly, & Sleegers, 2010;Mulford et al, 2004;Spillane, 2006;Spillane & Kim, 2012;Visscher & Witziers, 2004). Together, the three capacities (personal, interpersonal, and organizational) and their eight underlying dimensions form a conceptual model of PLCs that we will use to test the multidimensional, multilevel nature of PLCs within Dutch elementary schools.…”
Section: Modeling the Plc As A Multidimensional Multilevel Conceptmentioning
confidence: 99%
“…First, we included items and subscales from the Building Capacity for a Learning Community Questionnaire as developed by Sackney and colleagues (Sackney et al, 2005). In addition, we used items from the Professional Learning Community Assessment Questionnaire as developed by Huffman and Hipp (2003), as well as items from other existing instruments focused on leadership practices (Geijsel et al, 2009;Mulford et al, 2004). By combining these three questionnaires with a few newly designed items into one composite instrument, we covered the three capacities and eight underlying dimensions of the concept of PLCs suggested in our review of the literature (see Fig.…”
Section: Instrumentsmentioning
confidence: 99%
“…In the last two decades, a shift has taken place from 'transactional' leadership, wherein the exchange relationship between leaders and teachers is important (effort and productivity in exchange for rewards), to 'transformational leadership', which is characterised by leaders having the ability to give a clear vision for the future, to inspire employees, to stimulate employees to develop their talents in the best possible way, and to give their work a deeper meaning (De Hoogh et al 2004). Also from empirical work transformational leadership appeared to be an important predictor for professional development of teachers (Geijsel et al 2009;Runhaar, 2008).…”
Section: Organisational Conditions For Professional (Expertise) Develmentioning
confidence: 99%